2014
DOI: 10.1016/j.pscychresns.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carbamazepine on prefrontal activation in manic youth with bipolar disorder

Abstract: This preliminary study investigated the neurofunctional effects of carbamazepine-extended release (XR) treatment in 11 manic youth with bipolar disorder during performance of a sustained attention task, the Continuous Performance Task – Identical Pairs version, during functional magnetic resonance imaging (fMRI). All patients underwent baseline fMRI, and 10 patients were scanned again at endpoint. Nine demographically matched normal youth, who were scanned once, served as controls. Carbamazepine-XR treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…We could not determine whether the results that we observed were due to the effects of psychotropic drugs, although NIRS signals were not correlated with drug dosage. For example, a very recent study reported that carbamazepine extended-release treatment normalized frontopolar activation in manic youths with BD [55], and that postmortem brain tissue from medicated patients with BD exhibited impaired myelination in the frontopolar cortex [56]. Thus, there remains a possibility that the association found in this study was due to the treatment and the long-term course of the disorder.…”
Section: Discussionmentioning
confidence: 85%
“…We could not determine whether the results that we observed were due to the effects of psychotropic drugs, although NIRS signals were not correlated with drug dosage. For example, a very recent study reported that carbamazepine extended-release treatment normalized frontopolar activation in manic youths with BD [55], and that postmortem brain tissue from medicated patients with BD exhibited impaired myelination in the frontopolar cortex [56]. Thus, there remains a possibility that the association found in this study was due to the treatment and the long-term course of the disorder.…”
Section: Discussionmentioning
confidence: 85%
“…227 Treatment of mania with ziprasidone was associated with an increase in activation in the right ventrolateral prefrontal cortex in response to a sustained attention task, which suggests that the ziprasidone antimanic effect is associated with improved prefrontal modulation of emotional regulation. 228 Carbamazepine treatment of mania was also associated with increased activation in Brodmann area 10 of the right prefrontal cortex in a small sample of 11 adolescents, 229 further suggesting that mood stabilizers might exert their beneficial effects by improving the top-down prefrontal modulation of limbic areas. Treatment response to risperidone and divalproex sodium for mania may lead to increased functional connectivity of the amygdala within the ECN.…”
Section: | Neuroimaging and Neurocognitionmentioning
confidence: 99%
“…One approach toward extending these cross‐sectional studies is to identify how treatments have an impact on brain function in bipolar I disorder during the course of recovery from acute mood episodes . However, these types of studies, particularly of mania, are relatively rare and have often comprised small samples . In the context of an imaging study, mood stabilizers serve as useful neurobiological probes in order to identify brain activation changes during the process of recovery from acute affective episodes (i.e., treatment response) that might further clarify the functional neuroanatomy of bipolar illness.…”
mentioning
confidence: 99%
“…1 However, these types of studies, particularly of mania, are relatively rare and have often comprised small samples. [3][4][5][6][7][8] In the context of an imaging study, mood stabilizers serve as useful neurobiological probes in order to identify brain activation changes during the process of recovery from acute affective episodes (i.e., treatment response) that might further clarify the functional neuroanatomy of bipolar illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation